KINERJA PEGAWAI PADA AKADEMI KEBIDANAN KUDUS - Trisno Suwandi (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
Â This research aims to test the influence between discipline, organizational commitment, and communication on performance clerk Academy Midwifery Kudus in partial or double. The independent variables (non variable) in this research is the discipline (X 1), organizational commitment (X 2), communication (X 3). While the dependent Variable (the variable) is the performance of the employees (Y). The population used in this research was an employee at the Academy of the KudusÂ  of midwifery as much as 86 employees from the sample slovin formula taken as many as 46 respondents. Types and sources of data using primary data and secondary data. Method of collecting data using questionnaires. Processing the data using scoring, coding, editing, tabulating, and the process of with computer programs. Test instrument with test validity and reliability. The analysis of the data using analysis of descriptive and quantitative analysis include hypothesis testing, regression analysis (t-test and F-test), and the analysis of the coefficient of Determination (Adjusted R Square). Based on the results of the research there were partially positive and significant influence among variables of organizational commitment, discipline, and communication towards the performance of employees. Are there multiple positive and significant influence among variables of organizational commitment, discipline, and communication towards the performance of employees. The most dominant variables affect performance is variable organizational commitment.Keywords: discipline, organizational commitment, communication and performance